(2E)-2-[2-(Cyclohexylcarbamothioyl) hydrazinylidene]propanoic acid - Md. Abu, Affan; Md. Abdus, Salam; Fasihuddin B., Ahmad; Seik Weng, Ng; Edward R. T., Tiekink (International Union of Crystallography, 2011)
In the title thiourea derivative, C10H17N3O2S, the carboxyl group and the least-squares plane through the cyclohexyl ring are twisted out of the plane through the central CN3S residue; the respective dihedral angles are 7.18 (8) and 62.29 (4)°. The conformation about the azomethine bond [1.275 (2) Å] is E. The NH groups are anti, with one forming an intramolecular N—H⋯ N hydrogen bond. The main feature of the crystal structure is the formation of linear supramolecular chains along [110] mediated by alternating pairs of O— ...